Transient modelling of a loop thermosyphon : transient effects in single and two phase natural circulation thermosyphon loops suitable for the reactor cavity cooling of a pebble bed modular reactor - Ruppersberg, Johannes Coenraad (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScIng)--University of Stellenbosch, 2008.